PARENTAL ENGAGEMENT AND ACADEMIC ACHIEVEMENT IN EFL: A STUDY OF SAUDI INTERMEDIATE STUDENTS - Dahham Naji Al-Shammari (INJOSEDU: International Journal of Social and Education, 2025)
This study explores the effect of parental involvement on the academic performance of third intermediate students in English language in Saudi Arabian public schools. Employing a quasi-experimental design with pre- and post-tests, the study examined a sample of 113 male students divided into experimental and control groups from two schools in Qurayat. The experimental group's parents actively participated in the educational process, while the control group's parents did not. Results indicated statistically significant differences in post-test scores in favor of the experimental group, suggesting that parental engagement has a positive impact on students' English language achievement. The study concludes with recommendations to promote structured parental involvement and proposes further longitudinal research across diverse contexts.